Demineralized freeze-dried bone allograft vs biphasic calcium phosphate: A comparison of two graft materials in sinus augmentation procedures - A pilot study - Nishtha Gadkari; Shilpa Bawane; Ratima Chopra; Kalyani Bhate; Pushkar Waknis; Pradnya Kakodkar; Deepak Kulkarni; Paresh Kale (Elsevier, 2021)
Objective: To compare the bone quality histologically and radiologically using two graft materials i.e. demineralized freeze-dried bone allograft (DFDBA) and biphasic calcium phosphate (BCP) along with platelet-rich plasma (PRP) as an adjuvant in both; for bilateral maxillary sinus lift procedures. Material and methods: This split mouth pilot study consisted of 5 healthy patients who required bilateral sinus lift procedures in 10 sites. Allocation concealment for site selection was done. Site A was DFDBA with PRP and site B was BCP with PRP. Evaluation of bone density was done as per Misch criteria-preoperatively and 6 months postoperatively with CBCT scans. 6 months after the augmentation procedure, implants were placed and a trephine drill biopsy was taken, for histological evaluation of bone quality. Patients were followed up for 18 months after implant placement. Results: Five patients with a mean age of 47 ± 9.27 years (range of 35-60 years) underwent 10 maxillary sinus augmentation procedures. Radiologically, the bone density showed no statistically significant differences between site A: D4 and site B: D5; pre and post operatively. Histologically, the average value calculated for the percentage of marrow spaces was: site A, mean 40.92 ± 2.41 SD; site B mean: 31.48 ± 7.97 SD (t = 2.56, p = 0.03). The architecture of bone formed for all the 5 cases at site A was 100% trabecular pattern of bone, site B had 40% trabecular pattern of bone and 60% compact bone formation. Conclusion: Demineralized freeze-dried bone allograft with platelet rich plasma exhibited a superior quality of bone formation and a higher percentage of marrow spaces, it satisfied and met the evaluation parameters for bone quality. Clinical relevance: The conclusive findings of this research could guide clinicians towards utilising the amalgamation of DFDBA and PRP for bone augmentation procedures-as a safe and dependable option.